2015
DOI: 10.1038/nature14221
|View full text |Cite
|
Sign up to set email alerts
|

Cell-of-origin chromatin organization shapes the mutational landscape of cancer

Abstract: Cancer is a disease potentiated by mutations in somatic cells. Cancer mutations are not distributed uniformly along the genome. Instead, different genomic regions vary by up to 5-fold in the local density of somatic mutations1, posing a fundamental problem for statistical methods of cancer genomics. Epigenomic organization has been proposed as a major determinant of the cancer mutational landscape1-5. However, both somatic mutagenesis and epigenomic features are highly cell-type-specific6,7. We investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
494
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 525 publications
(548 citation statements)
references
References 29 publications
37
494
1
3
Order By: Relevance
“…The authors found that these variants are often located in or near enhancers [2][3][4][5][6][7][8][9] , and encompassing embryonic and adult tissues, from healthy individuals and those with disease. a, Many of the adult tissues investigated were broken down by cell type or region -blood into several types of immune cell, for instance, and the brain into regions including the hippocampus and dorsolateral prefrontal cortex.…”
Section: News and Viewsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors found that these variants are often located in or near enhancers [2][3][4][5][6][7][8][9] , and encompassing embryonic and adult tissues, from healthy individuals and those with disease. a, Many of the adult tissues investigated were broken down by cell type or region -blood into several types of immune cell, for instance, and the brain into regions including the hippocampus and dorsolateral prefrontal cortex.…”
Section: News and Viewsmentioning
confidence: 99%
“…For example, flanking sequences might have a topological role affecting chromatin packaging and, consequently, DNA accessibility. Polak et al 8 (page 360) investigated the distribution of cancer-associated genetic mutations in a set of diverse cancers, and correlated them with cell-type-specific epi genomic features. They found that the mutation profile of each cancer could often be predicted from the epigenomic signature of the cell type from which that cancer was most likely to have originated.…”
Section: News and Views Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…L'absence d'origines bien localisées serait ainsi une des causes de la fragilité de ces régions du génome [10][11][12]. Les délétions récurrentes et les régions où s'accumulent les mutations ponctuelles dans les cancers sont, pour la plupart, localisées dans des régions répliquées en fin de phase S [10,[13][14][15]. Inversement, les régions répliquées en début de phase S contiennent des régions fréquemment amplifiées [13][14][15].…”
Section: Perspectivesunclassified
“…Les délétions récurrentes et les régions où s'accumulent les mutations ponctuelles dans les cancers sont, pour la plupart, localisées dans des régions répliquées en fin de phase S [10,[13][14][15]. Inversement, les régions répliquées en début de phase S contiennent des régions fréquemment amplifiées [13][14][15]. Il existerait donc une relation, peutêtre causale, entre la densité en origines de réplication d'une région du génome et la nature des réarrangements chromosomiques que l'on observe dans les cancers.…”
Section: Perspectivesunclassified